PENGGUNAAN ASAS DISKRESI DALAM PEMBUATAN PRODUK HUKUM - Dinoroy Aritonang (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2010)
Government plays a prominent role in influencing many fields of life of society. The role is so much related to government’s functions in protecting and supporting people to get welfare in every side of life. Every step and policy considered and enacted by the government is indicated as government’s legal act and it will bind and influence social life vastly. There are two conditions when government’s legal act would be taken: in normal condition and in urgent one. In the first condition, government will take its legal act and policy according to clearer legal base and authority. However, it will be different in the latter condition, in which government has to face a real problem (sometimes) with no legal base and clearer authority but the problem should be solved immediately. In this case, discretionary principle in administrative law confers an authority for government’s officers to handlesuch kind of situation. But in principle too, there are a few legal and moral restrictions to use the power. The main purpose to restrict the use of power is not only to protect the people’s life from the arbitrariness of government but also to keep the principle of legal certainty.